CEDERA KEPALA PADA ANAK USIA DINI - Defni Satria (Program Studi Pendidikan Guru PAUD Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2019)
Early childhood often experience head injuries, this is due to high curiosity but is notsupported by physical motor skills. Head injuries are the highest cause of death and paralysis inchildren each year. More than 50 % of deaths are caused by head injuries and motorized accidents.Every year, more than 2 million people suffer head injuries, 75.000 of them die and more than100.000 people survive but have permanent disabilities. Head injury is a deformity in the form ofdeviation of shape or line on the skull, acceleration or deceleration which is a change in shapeinfluenced by an increase in the acceleration, and rotation ie the movement of the head is also feltby the brain as a result of rotation at the prevention level. It can be concluded that head injury is acondition where the brain experiences a collision causing interference with its fuction. The cause ofhead injury is divided into blunt trauma and trauma coup or contracoup. The level of awareness ofthe child after suffering a head injury can be assessed with GCS. This examination assesses thechildꞌs ability to follow instructions or respond to a physical stimulus. To avoid the child from havinga head injury, parents and PAUD teachers must really create a safe and comfortable environmentfor children both indoors and outdoors.